KONFLIK LAHAN ANTARA PT SEKAR BUMI ALAM LESTARI (PT. SA) DENGAN MASYARAKAT DI DESA KOTA GARO KECAMATAN TAPUNG HILIR KABUPATEN KAMPAR - Tunggul, M.Bintang; Hidir, Achmad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Soil has a role that is essential for human life, the need for land from day to day continues to increase and thus susceptible to a problems on land.Based on the above ideas, the writing task ahir is about land conflicts that occur between TP. Sekar Bumi Alam Lestari with the community in the City of Garo villages, in order to understand the forms of conflict, the causes of conflict and how the governments role in resolving the conflict.Expected by this research can determine (1) how where other forms of conflict between communities with the Company, (2) what causes the occurrence of a conflict and (3) how where the governments role in resolving the conflict in the village of Garo City.Conflicts in Rural Urban Garo include forms of conflict that resulted in violent conflict directly or indirectly violence and conflict vertical and horizontal conflict , whether the conflict between Garo City Village community with company PT . Sekar Bumi Alam Lestari or conflicts among fellow villagers in Kota Garo . Conflicts in Rural Urban Garo appear because a wide variety of factors that led to conflicts such as: needs, perceptions , power. So that led to conflict in the middle of the village community Garo City .keywords: land conflicts, Kota Garo Village